Stroke in a child with hemoglobin SC disease: a case report describing use of hydroxyurea after transfusion therapy - Diana Fridlyand; Caroline Wilder; E. Leila Jerome Clay; Bruce Gilbert; Betty S. Pace (MDPI AG, 2017)
Children with hemoglobin SC (HbSC) disease suffer a significant incidence of silent cerebral infarcts but stroke is rare. A 2-year-old African American boy with HbSC disease presented with focal neurologic deficits associated with magnetic resonance imaging evidence of cerebral infarction with vascular abnormalities. After the acute episode he was treated with monthly transfusions and subsequently transitioned to hydroxyurea therapy. The benefits of hydroxyurea as a fetal hemoglobin inducer in HbSC disease, to ameliorate clinical symptoms are supported by retrospective studies. This case highlights the rare occurrence of stroke in a child with HbSC disease and the use of hydroxyurea therapy.